Self and non-self discrimination affects the seedlings development of different kinship degrees under water deficit. - Bertolli, S. C. [UNESP]; Souza, G. M.; Edwards, D.; Oldroyd, G. (Elsevier B.V., 2015)
The strategy adopted by plants for exploit environments with low moisture may depend on the neighbor's identity. Roots of the plants have the ability to discriminate self (roots of the same plant) of non-self (roots of other plants), even without physical contact and while other plants are genetically identical. We investigated if there is any change in the plant behavior that self (Sd) and non-self (NSd) discriminate in situations of water limitation, and whether such behavior can be varied in individuals more or less kin. It was used two Eucalyptus urophylla groups: clones (high kinship-Hk); and population (low kinship-Lk). Split-root plants were planted so that each pot contained either two roots of the same plant (Sd) or of two different plants (NSd). The plants were subjected to full irrigation (Irr) or water deficit (WD) for thirty days, and biomass parameters of were evaluated. Plants of both groups and both discrimination conditions reduced their total dry mass (DMt) under WD. In Hk group, the WD increased the root/shoot ratio (23% compared to irrigated plants) by NSd, indicating that even when plants show a reduction in growth mediated by lack of water, there is an increase in biomass allocation to the roots when the plants interact each plants. In Hk group, the NSd reduced the dry mass (DMr) and volume (Vr) of roots only in Irr. In Lk group, DMt, DMr, Vr, and leaf area were reduced in NSd under Irr condition, whereas under WD, the NSd reduced just the specific leaf area (21% compared to Sd), indicating a change in biomass allocation to leaves. The results suggest that the discrimination is more evident in population group and in non-stressful environments, and although not so pronounced in situations of WD, these responses also occur as observed in Lk plants. (C) 2015 The Authors. Published by Elsevier B.V.
Keywords: Drought; Eucayptus urophylla; Kin recognition; Plant beaviour